Complementary Therapies and Factors Related to Dysmenorrhoea in Adolescents: A Bibliometric Analysis - Rejeki, Sri; Pranata, Satriya; Yanto, Arief; Wahyuni, Sri (Scripta Medica, 2024)
Complementary therapies for decreasing dysmenorrhoea and factors behind dysmenorrhoea in adolescents is not clear enough. Researchers need information about trends and novelties for the future research topic of complementary therapies and factors related to dysmenorrhoea in adolescents. Thus, the purpose of this study was to identify the complementary therapies for decreasing dysmenorrhoea and factors related to dysmenorrhoea in adolescents by analysing network visualisation, overlay visualisation and density visualisation on the topic through bibliometric analysis. The data sources used in this study were based on online searches via https://app.dimensions.ai/. The literature search used the stages following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flowchart. Paper restricted in publications years 2014-2023, focus in the field of health sciences, nursing, public health, clinical sciences and publication type were included as criteria for inclusion in the study. The data were analysed using VOSviewer. After identifying the clusters, the types of complementary therapies that were able to reduce dysmenorrhoea were acupressure, acupuncture, calcium sufficiency, curcumin, yoga, aromatherapy, massage and physical activity. Moreover, factors related to dysmenorrhoea were HIV, reproductive coercion, reproductive health, oxytocin, prolactin, trauma, metformin, anxiety and breast cancer. Moreover, the newest topics that were being widely researched related to adolescent dysmenorrhoea were education, non-suicidal self-injury (NSSI), prolactin and physical activity. On the other hand, topics that were rarely researched related to the topic of adolescent dysmenorrhoea were topics about sexual health, reproductive coercion, inflammation, curcumin and physical activity. Complementary therapies and factors that are still rarely studied offer potential novelty in results in future studies.